1989
DOI: 10.1136/gut.30.11.1563
|View full text |Cite
|
Sign up to set email alerts
|

Is a persistent adenovirus infection involved in coeliac disease?

Abstract: SUMMARY Recent evidence has implicated adenovirus 12 in the aetiology of coeliac disease so that persistent infection by this virus must be considered. We have undertaken a search for adenovirus DNA in duodenal biopsy samples from a total of 26 coeliac and non-coeliac patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…In 1984 it was observed that the EIB protein of human adenovirus type 12 shares sequence homology with an ␣-gliadin fragment [12]. However, no viral DNA nor antibodies specific for the EIB protein were found in patients [13][14][15]. Also, patient-derived T cells that are specific for the ␣-gliadin peptide do not cross-react with the homologous viral peptide (unpublished results).…”
Section: How Is Tolerance Broken?mentioning
confidence: 88%
“…In 1984 it was observed that the EIB protein of human adenovirus type 12 shares sequence homology with an ␣-gliadin fragment [12]. However, no viral DNA nor antibodies specific for the EIB protein were found in patients [13][14][15]. Also, patient-derived T cells that are specific for the ␣-gliadin peptide do not cross-react with the homologous viral peptide (unpublished results).…”
Section: How Is Tolerance Broken?mentioning
confidence: 88%
“…Several studies suggested a link between certain viruses and enteropathy ( Table 3). As these observations were made in singular patients [63,89,98], or contradicted by findings of other research groups [62,107,108], the relation remains uncertain. Studies describing enteropathy in PID patient groups (mostly antibody deficiencies) did not address the presence of enteric viruses in feces or gastrointestinal tract biopsy specimens [124][125][126][127][128][129], although Daniels et al [130] found cytomegalovirus in a few CVID patients, which coincided with the presence of intraepithelial neutrophils.…”
Section: Discussionmentioning
confidence: 67%
“…Neutralizing antibodies to adenovirus 12 were found in 80% of untreated celiac patients, compared to 33% and 31% in treated adults and children, respectively, and 0-13% healthy controls [106]. Conversely, studies on the presence of adenovirus 12 DNA on duodenal biopsy samples of celiac disease patients found no evidence for a role in the pathogenesis of celiac disease [107,108]. Second, adenovirus may play a role in HIV enteropathy [109], defined as enteropathy in HIVpositive patients after exclusion of other pathogens [110][111][112].…”
Section: Adenovirusmentioning
confidence: 84%
“…In 1991, Mantzaris and Jewell23 demonstrated that intraduodenal insertion of the peptide produced mononuclear cell infiltration and microscopic changes that were not seen in controls. However, later studies using monoclonal antibodies against the epitope sequence24 and studies looking for persistent adenovirus DNA25 26 in small intestinal biopsies have failed to show evidence of an association.…”
Section: Adenovirus 12 In Coeliac Diseasementioning
confidence: 99%